The social and psychological problems experienced by the elderly (elderly) in old age (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study deals with the most important problems related to the age of aging, especially the social - psychological ones, which appear little by little as the age of man, and from the increase in this segment on the one hand, and then seek to help the elderly and solve their problems on the other hand. This study deals with several aspects: First: the concept of aging, its limits, its manifestations, second: the fertility that characterizes this stage, the social problems of the elderly, the psychological problems of the elderly, Problems of older persons. In conclusion, they made several proposals in order to contribute to the goal of the study to focus attention on the elderly and to understand their various problems in order to move towards solving them.